2022
DOI: 10.1002/ldr.4476
|View full text |Cite
|
Sign up to set email alerts
|

Biocrust diversity enhances dryland saline soil multifunctionality

Abstract: Biocrusts are multifaceted communities including mosses, lichens, and cyanobacteria that are crucial for sustaining soil functions in drylands. Most studies on biocrust functions to date have focused on biocrust cover and development, largely in nonsaline soils, and we know very little about the importance of biocrust diversity for maintaining multifunctionality in saline dryland soils. We assessed the direct and indirect linkages between biocrust richness, soil texture and salinity and soil multifunctionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…The assay methods are described in the Supplementary document . This study focused on the topsoil because many previous studies have focused on the topsoil ( Allison et al, 2015 ; Ding et al, 2020 ; Kakeh et al, 2022 ). Moreover, a recent study found that shrub expansion altered the microbial community in the topsoil rather than in the subsoil ( Droma et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay methods are described in the Supplementary document . This study focused on the topsoil because many previous studies have focused on the topsoil ( Allison et al, 2015 ; Ding et al, 2020 ; Kakeh et al, 2022 ). Moreover, a recent study found that shrub expansion altered the microbial community in the topsoil rather than in the subsoil ( Droma et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The methods of determination and calculation were described in our previous research ( Ding et al, 2020 ) and in the Supplementary document . These individual functions were included in the multifunctionality because they are either real functions or good markers of ecosystem functions and have been frequently used to quantify ecosystem multifunctionality in recent studies ( Manning et al, 2018 ; Ding and Wang, 2021 ; Guan et al, 2022 ; Kakeh et al, 2022 ; Ding et al, 2023 ; Jia et al, 2023 ; Luo et al, 2023 ; Yang et al, 2023a ).…”
Section: Methodsmentioning
confidence: 99%